The Use of Kaili Regional Language in Improving Learning Outcomes in PAI Subjects - Muhammad Rizal Masdul; Rahmawati; Feri Payuhi; Adriansyah A. Lasawali (Universitas Muhammadiyah Palu, 2022)
This study aims to determine the useof Kaili Regional Language in Improving Learning Outcomes in PAI Subjects at SDN 26 South Banawa